Predicting the frequencies of drug side effects - Diego Galeano (Nature Portfolio, 2020)
Currently, the frequencies of drug side effects are determined in randomised controlled clinical trials. Here the authors develop an interpretable machine learning approach to predict the frequencies of unknown side effects for drugs with a small number of determined side effect frequencies.